Trade-induced forest-to pasture conversion in Brazil: Insights from the global beef supply chains - Chen, Ziqi; Chen, Shuai; Chen, Kevin Z. (CGIAR System Organization, 2025)
International trade is a defining feature of contemporary food systems and can generate substantial environmental pressures in tropical forest regions. This study examines how demand transmitted through global beef supply chains is associated with forest-to-pasture conversion in Brazil. Using panel data for 5,570 Brazilian municipalities from 2013 to 2020, we integrate supply-chain information with satellite-based land-use data to estimate the effects of beef export exposure on forest-to-pasture conversion, exploiting exogenous variation in export demand. We find that a 1% increase in Brazilian beef exports to China is associated with a 0.0194% increase in forest-to-pasture conversion in Brazil, while a 1% increase in Brazilian beef exports to the European Union and the United Arab Emirates are associated with a 0.0547% and 0.0227% increase, respectively, in forest-to-pasture conversion. These comparative analyses across major destination markets suggest that trade–forest relationships vary across markets and local contexts rather than being driven by a single importing country. These effects are spatially heterogeneous, with stronger impacts in economically less developed municipalities and in areas with limited remaining forest cover. Together, the results highlight how demand shocks transmitted through global food supply chains can shape land-use dynamics in tropical forest countries, underscoring the importance of aligning trade and food system policies with forest conservation objectives.